Qualitative research in education : a user's guide - Lichtman, Marilyn (Los Angeles, California : Sage Publications, Incorporation, 2013)
This textbook provides readers with a blend of practical and theoretical information, using real-world examples and illustrations to help users grasp abstract ideas and apply them to their research.
Part I. Traditions and Influences -- Chapter 1. Introduction and Overview of the Field -- Chapter 2. Learning How to Be a Qualitative Researcher -- Chapter 3. Ethical Issues in Qualitative Research -- Chapter 4. Designing Your Research: Five Popular Research Approaches -- Chapter 5. Designing Your Research: Additional Research Approaches -- Part II. Gathering, Organizing, and Analyzing -- Chapter 6. Social Media, the Internet, and Technology -- Chapter 7. Embarking on Qualitative Research -- Chapter 8. Reflexivity and Subjectivity -- Chapter 9. The Role and Function of a Literature Review -- Chapter 10. Learning About Others Through Interviewing -- Chapter 11. Learning About Others Through Observations and Other Techniques --Part III. Putting It All Together -- Chapter 12. Making Meaning From Your Data -- Chapter 13. Communicating Your Ideas -- Chapter 14. Judging and Evaluating -- Chapter 15. Thinking About the Future.
Includes index.
Keywords: EDUCATION